TECHNOLOGY FOR DEVELOPING THE METHODOLOGICAL COMPETENCE OF FUTURE MORAL EDUCATION TEACHERS BASED ON AN ERGONOMIC APPROACH (A CASE OF THE PEDAGOGICAL EDUCATION PROGRAM) - Usmonova Hafiza Kodirjonovna (Bright Mind Publishing, 2025)
The modernization of higher pedagogical education necessitates the development of effective educational technologies that ensure the formation of professionally competent, adaptable, and resilient teachers capable of responding to contemporary educational challenges. In this context, the methodological competence of future moral education (tarbiya) teachers represents a key professional quality that determines the effectiveness of moral, civic, and value-oriented instruction. This study aims to develop and substantiate a pedagogical technology for enhancing the methodological competence of future moral education teachers based on an ergonomic approach, using the pedagogical education program as a representative case. The ergonomic approach is conceptualized as a human-centered pedagogical strategy that optimizes the interaction between students, instructional content, teaching methods, and educational conditions. The research employs a competence-based and technological framework, integrating theoretical modeling, pedagogical diagnostics, and experimental implementation. The proposed technology is structured into interrelated stages—diagnostic, design, implementation, and reflective-evaluative—each aligned with ergonomic principles such as cognitive load optimization, emotional comfort, instructional clarity, and methodological adaptability. The findings indicate that the implementation of ergonomic-based pedagogical technology significantly improves students’ motivational engagement, methodological flexibility, and reflective competence. The study contributes to pedagogical theory by elaborating the technological dimension of ergonomic competence development and offers practical guidance for higher education institutions involved in training future moral education teachers. The results confirm that ergonomic-based educational technology constitutes an effective and sustainable mechanism for advancing methodological competence within pedagogical education programs.
Keywords: Pedagogical technology; methodological competence; ergonomic approach; moral education teachers; pedagogical education; teacher training technology; competence-based learning.